2003
DOI: 10.1002/humu.10170
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of anLMNAmutation associated with a new cardiac and non-cardiac phenotype

Abstract: Heritable dilated cardiomyopathy is a genetically highly heterogeneous disease. To date 17 different chromosomal loci have been described for autosomal dominant forms of dilated cardiomyopathy with or without additional clinical manifestations. Among the 10 mutated genes associated with dilated cardiomyopathy, the lamin A/C (LMNA) gene has been reported in forms associated with conduction-system disease with or without skeletal muscle myopathy. For the first time, we report here a French family affected with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 36 publications
(32 reference statements)
0
48
0
Order By: Relevance
“…Histological examination confirmed cardiomyopathy, but did not reveal any specific pattern for LMNA mutant carriers. However, immunohistochemistry has been shown to detect altered lamin A/C expression in patients carrying LMNA mutations [41], which is similar to the in vitro observations in transfected cells [42]. At this point, there is not enough information available to speculate on any genotype/phenotype correlation.…”
Section: Discussionmentioning
confidence: 71%
“…Histological examination confirmed cardiomyopathy, but did not reveal any specific pattern for LMNA mutant carriers. However, immunohistochemistry has been shown to detect altered lamin A/C expression in patients carrying LMNA mutations [41], which is similar to the in vitro observations in transfected cells [42]. At this point, there is not enough information available to speculate on any genotype/phenotype correlation.…”
Section: Discussionmentioning
confidence: 71%
“…The exact pathophysiological mechanism of LMNA mutations that lead to such an impressive heterogeneous spectrum of disorders has not yet been elucidated. However, myocardial fibrosis as a secondary phenomenon has been described before in different laminopathies (10,15,33). The identified deletion of the 5' end of the LMNA gene containing the start codon is predicted to affect mainly the head domain of lamin (that is, it might lead to a shortened protein lacking the head domain).…”
Section: Discussionmentioning
confidence: 96%
“…The only relationship that has emerged so far has been reported by Benedetti et al [32], who showed that patients with early skeletal muscle involvement carry essentially missense mutations, whereas patients presenting with a later onset of their muscle symptoms carried frameshift mutations, presumably leading to truncated proteins. However, the same mutation within a single family can give rise to variable phenotypes [14,15,[33][34][35][36][37][38], suggesting that, besides LMNA mutation, additional players are involved to account for this variability. Among these players, digenism has been reported in a few cases that may explain in part this variability.…”
Section: Striated Muscle Laminopathiesmentioning
confidence: 99%